2012
DOI: 10.1038/oby.2012.65
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exercise and Training Alter Blood Lipid and Lipoprotein Profiles Differently in Overweight and Obese Men and Women

Abstract: Our purpose was to elucidate effects of acute exercise and training on blood lipids‐lipoproteins, and high‐sensitivity C‐reactive protein (hsCRP) in overweight/obese men (n = 10) and women (n = 8); age, BMI, body fat percentage, and VO2max were (mean ± SEM): 45 ± 2.5 years, 31.9 ± 1.4 kg·m−2, 41.1 ± 1.5%, and 25.2 ± 1.3 mlO2·kg−1·min−1. Before exercise training subjects performed an acute exercise session on a treadmill (70% VO2max, 400 kcal energy expenditure), followed by 12 weeks of endurance exercise train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
41
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 39 publications
14
41
1
1
Order By: Relevance
“…In our study, exercise led to improvements in lipids profile as well. In agreement with our results, Greene et al also reported that obese middle-aged men and women participating in endurance exercise at 70% of VO2max, 3 times per week for 12 weeks had significant improvements in lipid profiles [58]. Sung & Bae reported a similar finding in diabetic elderly men participating in walking exercise at 65-75% of HRmax for 50 minutes a day, 3 times a week for 24 weeks [59].…”
Section: Discussionsupporting
confidence: 82%
“…In our study, exercise led to improvements in lipids profile as well. In agreement with our results, Greene et al also reported that obese middle-aged men and women participating in endurance exercise at 70% of VO2max, 3 times per week for 12 weeks had significant improvements in lipid profiles [58]. Sung & Bae reported a similar finding in diabetic elderly men participating in walking exercise at 65-75% of HRmax for 50 minutes a day, 3 times a week for 24 weeks [59].…”
Section: Discussionsupporting
confidence: 82%
“…We have shown that hsCRP is elevated after a marathon race -similar to those reported by Kim et al (Kim, Lee, & Kim, 2009) -independent of BMI. However, the increase in hsCRP in our study (+1.5mg/ml) was smaller than that reported by Greene et al (Greene, Martin, & Crouse, 2012) (+5.0 mg/ml) who reported elevated hsCRP in overweight and obese persons 24 hours after acute exercise regardless of training. Nonetheless, hsCRP in some participants exceeded values considered as risk factor for cardiovascular disease (above 3.0 mg/L (Ridker & Libby, 2007)) 24 hours after the marathon race.…”
Section: Il-6 Is a Pro-inflammatory Cytokine Secreted By T-cells And contrasting
confidence: 56%
“…The results of numerous studies [30][31][32][33][34][35], indicate that moderate physical exercise increases the plasma values of c-HDL and it reduces the plasma values of TG and c-LDL. Nevertheless, the type, intensity, frequency, and the ideal duration of the physical exercise, are variables that are not yet widely agreed upon.…”
Section: Discussionmentioning
confidence: 99%
“…A persistent increase in glycaemia results in the storage of glucose in the liver in the form of glycogen. This is emitted later into the circulatory system and through glycolysis is transformed into coenzyme A, capable of binding to proteins and thus gives rise to lipoproteins, which would explain the increase of c-LDL that is experienced in this situation [30][31][32].…”
Section: Discussionmentioning
confidence: 99%